Floristic Composition, Diversity, and Regeneration of Woody Plant Species of Dabal Forest in Southeastern Ethiopia: Implication for Conservation - Zinab Sherafu; Meseret C. Egigu; Sasikumar J. M. (Scientifica)
Floristic composition, population structure, and regeneration status of woody species of Dabal forest found in East Hararghe zone of Oromia Regional State, Ethiopia, were studied. Vegetation data were obtained from 52 main plots of 20 × 20 m for mature woody species and 5 subplots of 5 × 5 m for seedlings and saplings. Density and dbh of each live woody plant species found in each sample plot were recorded. Frequency, basal area, importance value, and Shannon–Wiener diversity indices were also computed. Totally 59 woody plant species distributed in 33 families were documented. Of these, 45.80, 44.10, and 5.08% were shrubs, trees, and lianas, respectively. Species diversity and evenness indices were 3.56 and 0.87, respectively. Stem count of all woody species was 3379 stems ha−1. Out of this, 44.6, 30.8, and 24.59% were seedlings (dbh <3.5 cm), saplings (dbh between 3.5 and 10 cm), and mature (dbh >10 cm) individuals, respectively. Total basal area of all individuals with dbh ≥3.5 cm was 29.88 m2 ha−1. Juniperus procera, Cupressus lusitanica, Eucalyptus globulus, Afrocarpus falcatus, Eucalyptus camaldulensis, Myrsine africana, Maytenus undata, Hagenia abyssinica, Ekebergia capensis, and Cordia africana were species with top ten IVI. Most of these species were top densest, dominant, and frequent. Analysis of population structure based on pooled densities of all species in each dbh class showed that density of seedling > sapling > mature individuals, signifying healthy population structure with good natural regeneration potential. On individual basis, however, 35.6 and 8.5% of species showed fair and poor regeneration statuses, respectively, that deserve attention for conservation.